Is Kazakhstan vulnerable to the Dutch disease? - Karlygash Kuralbayeva; Ali M. Kutan; Michael L. Wyzan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
Kazakhstan possesses extensive natural resources reserves that are expected to yield significant export revenues. Since Kazakhstan's attaining independence in 1991, the composition of exports has changed in favor of energy-related sectors. In the context of such evidence and considerable expected future revenues, many researchers have pointed to the Dutch Disease question. This paper examines whether Kazakhstan is vulnerable to this condition. Using an extended version of the Balassa-Samuelson model including a terms-of-trade effect, we find evidence that changes in the terms of trade had a significant effect on the real exchange rate after 1996, providing evidence of the Dutch Disease.
Keywords: 330; Dutch Disease; transition; oil; terms of trade; Kazakhstan; Dutch Disease; Kasachstan